ANALISIS YURIDIS HAK WARIS ANAK LUAR KAWIN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 - NIM. A1011181039, NOVRITA INDRIASWARI (Fakultas Hukum Universitas Tanjungpura, 2022)
AbstractGenerally, a parent must be responsible for the life of their child. The existence of a child born where not from a marriage bond legitimate or children born from marriages that are not registered in the authorized agency is known as the